(untitled) (Archives of Mechanics - Test, 2005)
Editor of the Archives of Mechanics (1970-1981) On October 25th, 2004, Professor Władysław Fiszdon, an outstanding scientist, expert on aerodynamics, aviator and mathematician died in Warsaw. Science has thus suffered a painful loss and all who knew Him have lost a man of extraordinary mind and character. Everything that He has done for the Science, especially for development of the Fluid Mechanics, will remain forever in our memory and in the memory of future generations.